ANALISA TINGKAT KEPUASAN PENGGUNA TERHADAP APLIKASI GOPAY MENGGUNAKAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Muhammad Aditya Rizka; Sari Dewi; Dwi Yuni Utami (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Digital technology is a development in information technology that suppresses the use of electronic or digital devices. Currently, the use of digital payments is increasingly popular and has become a daily necessity, according to statistical data on the use of digital wallets. One application that supports digital payment services is the Gopay application, a popular electronic money or e-wallet service in Indonesia which has more than 10 million users. Gopay aims to provide millions of families in Indonesia with access to various financial services and products. Payment transactions at SEBASA have implemented non-cash payments, where most SEBASA residents use digital payments daily with the Gopay application as the main choice. In order for transaction activities at SEBASA to be optimal, the application used must be able to meet user needs efficiently. Therefore, assessing user satisfaction with the Gopay application in the SEBASA environment is very important to identify how well Gopay meets these needs and to increase productivity and efficiency at SEBASA. One method for analyzing the level of user satisfaction with aGopay application is by applying the TAM method. Researchers obtained data from distributing questionnaires consisting of 3 TAM variables, namely Perceived Ease of Use (X1), Perceived Effectiveness (X2), Behavioral Intention to Use (Y). The research results show that the level of satisfaction of Gopay application users is very good. Partially, the variables Perceived Ease of Use (X1) and Perceived Effectiveness have a significant influence on user satisfaction. And together (simultaneously) the independent variables have a significant effect on the dependent variable.